Advances in computing and network communications Volume 2 proceedings of CoCoNet 2020 - Thampi, Sabu M.; Gelenbe, Erol; Atiquzzaman, Mohammed; Chaudhary, Vipin; Li, Kuan-Ching (Singapore Springer, 2021)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Conference on Computing and Network Communications (CoCoNet'20), October 14–17, 2020, Chennai, India. The papers presented were carefully reviewed and selected from several initial submissions. The papers are organized in topical sections on Signal, Image and Speech Processing, Wireless and Mobile Communication, Internet of Things, Cloud and Edge Computing, Distributed Systems, Machine Intelligence, Data Analytics, Cybersecurity, Artificial Intelligence and Cognitive Computing and Circuits and Systems. The book is directed to the researchers and scientists engaged in various fields of computing and network communication domains.
Part 1: Machine Learning, Visual Computing and Signal Processing -- Chapter 1. Computational Reconstructions of Extracellular Action Potentials and Local Field Potentials of a Rat Cerebellum using Point Neurons -- Chapter 2. Iris Recognition using Integer Wavelet Transform and Log Energy Entropy -- Chapter 3. Deep Learning Based Approach for Skin Burn Detection with Multi-level Classification -- Chapter 4. Semantic Retrieval of Microbiome Information Based on Deep Learning -- Chapter 5. Early Detection of Covid-19 on CT Scans Using Deep Learning Techniques -- Chapter 6. Towards Protein Tertiary Structure Prediction using LSTM/BLSTM -- Chapter 7. An Android Based Smart Home Automation System in Native Language -- Chapter 8. Live Acoustic Monitoring of Forests to Detect Illegal Logging and Animal Activity -- Chapter 9. CATS: Cluster-Aided Two-Step Approach for Anomaly Detection in Smart Manufacturing -- Chapter 10. Prediction of Energy Consumption using Statistical and Machine Learning Methods and Analysing the Significance of Climate and Holidays in the Demand Prediction -- Chapter 11. Ranking of Educational Institutions based on user priorities using AHP-PROMETHEE Approach -- Chapter 12. Using AUDIT Scores to Identify Synbiotic Supplement Effect in High Risk Alcoholics -- Chapter 13. Accurate Identification of Cardiac Arrhythmia using Machine Learning Approaches -- Chapter 14. Learning based Macro Nutrient Detection Through Plant Leaf -- Chapter 15. Characteristics of Karawitan Musicians' Brain: sLORETA Investigation.
Electronic reproduction
Keywords: Computer science -- Congresses; Computer networks -- Congresses; Electronic books